Adaptation, Validation and Preliminary Standardisation of the Frontal Systems Behaviour Scale – Apathy Subscale and the Dimensional Apathy Scale in Vietnamese Healthy Samples. (23rd March 2022) - Quang, Halle; Sin, Khanh; Kumfor, Fiona; McDonald, Skye
Abstract: Objective: Apathy, the reduction of motivation and goal-directed behaviour, is a ubiquitous behavioural syndrome in many neurological disorders. However, apathy measures are limited in non-English speaking countries. The present study aimed to develop a culturally appropriate version of the Vietnamese Frontal Systems Behavioural Scale-Apathy subscale (V-FrSBe-A) and Dimensional Apathy Scale (V-DAS), examine their internal reliability and construct validity (i.e., factor structure, convergent and divergent validity) in a Vietnamese healthy sample and establish preliminary normative cut-offs for clinical and research applications. Method: In total, 112 healthy subjects and 64 informants completed the self-report and informant report V-FrSBe-A and V-DAS, developed using a translation, back-translation and cultural adaptation procedure. McDonald's omega was applied to examine internal reliability. The internal structure of the V-DAS was evaluated using exploratory structural equation model. For both apathy scales, convergent validity was determined by correlations between scales and between informant and self-report versions. Regarding divergent validity, participants completed the Vietnamese Depression Anxiety Stress Scale-21 and V-FrSBe-Disinhibition for depression and disinhibition assessment. Results: Both the V-FrSBe-A and V-DAS were reliable ( ω t ≥ .74). Dimensional manifestations of apathy in executive, emotional and initiation domains were confirmed on the V-DAS. Both scales were also valid, convergent with each other and divergent from depression and disinhibition symptoms. Cut-off scores for both scales were higher than their English versions. Conclusion: The adapted V-FrSBe-A and V-DAS have good reliability and validity for the potential application in clinical groups to advance current knowledge about apathy transculturally and direct more effective clinical care for Vietnamese individuals with neurological disorders.